Operational Operational Analysis of Waste Transportation in Sukarami District to Sukawinatan Final Disposal - Ani Firda Martawi; Rosmalinda Permatasari; Destu Lareza (Research Centre of Inorganic Materials and Complexs, 2019)
Increased development, economic growth and population growth in Sukarami Sub-district also have an impact on changes in the lifestyle of its people, which are becoming more consumptive. This has led to an increase in waste production, which must be managed properly, especially in transportation to the landfill. The purpose of this study was to count the number of dump trucks needed to transport the garbage produced in Sukarami District to the final disposal site of the Sukawinatan landfill. The data collected in this study were survey data on the generation of waste per capita and the number of residents to calculate the waste generation in Sukarami District , as well as survey data on waste transportation, namely the capacity of the garbage truck, the time to load and reduce waste, travel time, travel distance, and route of travel. Secondary data collected is a map of Sukarami Subdistrict, transport vehicle routes, the number of garbage transport equipment in the form of dump trucks, the population, and the number of markets. Obtained results that large generationSolid waste generated in Sukarami District in 2019 is 427,873 m3 / day, and is predicted to increase to 450,367 m3 / day in 2023. The need for garbage transport vehicles is 29 units of dump trucks. The number of trips needed for dump trucks is 57 trips / day from 2019 - 2023, 61 trips / day for 2023. Keywords waste generation, transportation system , Sukarame District.